2016
DOI: 10.1089/lap.2016.0031
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Laparoscopic Bean Vaginoplasty (Modified Vecchietti Procedure) for Mayer–Rokitansky–Kuster–Hauser Syndrome

Abstract: LBV is a successful modification of Vecchietti procedure, without any reported complication. However, the procedure should still be compared with the other methods in randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…El paso de los hilos a través de una aguja desde el periné nos ha parecido más simple, cuando la comparamos con el paso desde la cavidad abdominal. Esta variante es descrita en otras publicaciones (13). La tensión diaria y la incomodidad del porte del retractor obligan a una hospitalización prolongada, la cual podría ser reducida con hospitalización en casa.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El paso de los hilos a través de una aguja desde el periné nos ha parecido más simple, cuando la comparamos con el paso desde la cavidad abdominal. Esta variante es descrita en otras publicaciones (13). La tensión diaria y la incomodidad del porte del retractor obligan a una hospitalización prolongada, la cual podría ser reducida con hospitalización en casa.…”
Section: Discussionunclassified
“…A largo plazo, informan 5 estenosis y 3 casos de granuloma, complicaciones también presentes en nuestro estudio. Cetin, en Turkia, en 62 casos tampoco informa complicaciones serías con esta técnica (13).…”
Section: Discussionunclassified
“…Cetin et al reported the long-term follow-up of 62 patients who underwent the modified Vechietti procedure; no complications were noted, while a median vaginal length of 7 cm was achieved [160]. In addition, sexual function as assessed with the FSFI questionnaire was similar to age-matched controls [160].…”
Section: The Vecchietti Proceduresmentioning
confidence: 96%
“…A team from Germany reported a 16-month follow-up of 240 patients who underwent a modified Vecchietti procedure for neovagina creation; shorter operation and traction times, better functional results, and fewer surgical long-term complications were noted compared to the traditional laparoscopic Vecchietti procedure [158,159]. Cetin et al reported the long-term follow-up of 62 patients who underwent the modified Vechietti procedure; no complications were noted, while a median vaginal length of 7 cm was achieved [160]. In addition, sexual function as assessed with the FSFI questionnaire was similar to age-matched controls [160].…”
Section: The Vecchietti Proceduresmentioning
confidence: 99%
“…The formation of a new vagina can be performed by surgical creation of a tunnel between the bladder and rectum using a skin graft (McIndone method), use of the intestine, peritoneum, amnion, allogenic epidermis, autologous cheek mucosa, or cultured invitro autologous vaginal tissue [ 39 ]. Currently, the most popular methods of laparoscopic neovagina formation are Vecchietti´s and Davydov´s methods.…”
Section: Congenital Defectsmentioning
confidence: 99%